The Role of the Neuro-Astro-Vascular Unit in the Etiology of Ataxia Telangiectasia - Meshulam, Leenoy; Galron, Ronit; Kanner, Sivan; De Pitta', Maurizio; Bonifazi, Paolo; Goldin, Miri; Frenkel, Dan; Ben-Jacob, Eshel; Barziali, Ari (Frontiers in Pharmacology, 2012)
The growing recognition that brain pathologies do not affect neurons only but rather are, to a large extent, pathologies of glial cells as well as of the vasculature opens to new perspectives in our understanding of genetic disorders of the CNS. To validate the role of the neuron-glial-vascular unit in the etiology of genome instability disorders, we report about cell death and morphological aspects of neuro-glia networks and the associated vasculature in a mouse model of Ataxia Telangiectasia (A-T), a human genetic disorder that induces severe motor impairment. We found that AT-mutated protein deficiency was consistent with aberrant astrocytic morphology and alterations of the vasculature, often accompanied by reactive gliosis. Interestingly similar findings could also be reported in the case of other genetic disorders. These observations bolster the notion that astrocyte-specific pathologies, hampered vascularization and astrocyte-endothelium interactions in the CNS could play a crucial role in the etiology of genome instability brain disorders and could underlie neurodegeneration.